Recent tissue engineering-based advances for effective rAAV-mediated gene transfer in the musculoskeletal system. Issue 3 (8th April 2016) - Rey-Rico, Ana; Cucchiarini, Magali
ABSTRACT: Musculoskeletal tissues are diverse and significantly different in their ability to repair upon injury. Current treatments often fail to reproduce the natural functions of the native tissue, leading to an imperfect healing. Gene therapy might improve the repair of tissues by providing a temporarily and spatially defined expression of the therapeutic gene(s) at the site of the injury. Several gene transfer vehicles have been developed to modify various human cells and tissues from musculoskeletal system among which the non-pathogenic, effective, and relatively safe recombinant adeno-associated viral (rAAV) vectors that have emerged as the preferred gene delivery system to treat human disorders. Adapting tissue engineering platforms to gene transfer approaches mediated by rAAV vectors is an attractive tool to circumvent both the limitations of the current therapeutic options to promote an effective healing of the tissue and the natural obstacles from these clinically adapted vectors to achieve an efficient and durable gene expression of the therapeutic sequences within the lesions.